Lipoatrophic panniculitis and chromosome 10 abnormality. - Moramarco, F.; Garofalo, L.; Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 7-month-old child was first observed for the presence of numerous inflammatory nodules on the limbs, in the absence of general symptoms. The nodules presenting a diameter between 1 and 6 cm had a centrfugal evolution leaving centrally a deep depression due to atrophy of the fat tissue. Laboratory tests ruled out autoimmune diseases and histological examination showed a lobular panniculitis with atrophy of the fat tissue. The genetic tests showed a karyotype 46, XY, t (10; 18) (P12.2, q 21:33) and the presence of a seemingly balanced reciprocal translocation involving chromosomes 10 and 18. The array-CGH analysis highlighted duplication of the 10p15.3p12.2 region with a size of about 23 Mb and deletion of the 18q21.33q23 region with a dimension of about 17.5 Mb. The child responded very well to the administration of deflazacort 1 mg/kg per day with disappearance in a few days of the inflammatory nodules, while atrophy of the fat tissue still persisted. A review of the literature showed a case similar to ours associated with alteration of chromosome 10. Therefore, such an association appears to play a causal role in the disease.